Dinitrochlorobenzene (DNCB) In The Treatment Of Warts - Chattopadhyay S. P (Wolters Kluwer Medknow Publications, 2001)
Forty patients (male-25, female-15) of age group 15 to 46 years (mean 23 years) were attempted for contact sensitization with 0.5% -3% dinitrochlorobenzene (DNCB) solution. Thirty five cases could be hypersensitized. Out of these cases, 11(27.5%)cases responded fully with subsequent local application of 0.5-1% DNCB solution on the warts and another 32.5% cases showed moderate response while 40% of cases did not show any response. It was also seen that 77.5% of patients suffered from moderate to severe complication in the form of eczematous reaction. Pain and induration both on the site of hypersensitization and on sites away from it. The eczematous reaction subsided slowly over 2 to 4 weeks period without leaving any permanent scar. DNCB (topical) could be used for a cure under direct supervision in the selected cases of verrucae not responding to standard treatment by initial sensitization and thereafter direct application over the warts. There was a marginal increased tuberculin (PPD) response after hypersensitization process with DNCB.